EFEKTIVITAS HOME VISIT TERHADAP MOTIVASI BELAJAR SISWA KELAS X MA ISLAMIYAH MALO TAHUN PELAJARAN 2023/2024 - M.Pd, iswahyuni; Sigit Widodo, Bambang; Sri utami, Wiwik; Perdana Prasetya, Sukma; Lestari Sitohang, Lidya (Jurnal Pendidikan : Riset dan Konseptual, 2026)
Low student learning motivation remains a critical issue that hinders academic achievement in Islamic schools. This study investigates the effectiveness of a home visit program in enhancing the learning motivation of tenth-grade students at MA Islamiyah Malo during the 2023/2024 academic year. A quasi-experimental design with a pretest-posttest control group was employed, involving 60 students divided into an experimental group (n=30) and a control group (n=30). Data were collected using a validated learning motivation scale and in-depth interviews. Quantitative data were analyzed through descriptive and inferential statistics using SPSS 26, including Shapiro-Wilk normality tests, Levene’s test for homogeneity of variances, independent sample t-tests, and paired sample t-tests. Qualitative data were analyzed thematically following Braun and Clarke’s framework. Results revealed a statistically significant increase in learning motivation in the experimental group (20.87%) compared to the control group (4.95%). The intervention demonstrated a large effect size (Cohen’s d = 1.493, p < 0.001). Thematic analysis highlighted four key dimensions: enhanced personal attention, stronger parental involvement, improved learning environments, and the development of intrinsic motivation. Overall, the findings indicate that home visits are effective in fostering student learning motivation by strengthening family-school communication and optimizing supportive learning contexts that address students’ basic psychological needs.